Therapy For Unilateral Lower Extremity Lymphedema With Compression Bandage Only Or Compression Bandage Combined With Surgery - Hakim, Intan Frischilla; Sudjatmiko, Gentur (Jurnal Plastik Rekonstruksi, 2012)
Background: Lymphedema on lower extremity is a disorder which is still hard to manage nowadays. Many therapeutic modalities had been done, but there weren’t any satisfying outcome. It is all due to the continuous exudation of the lymph which is rich in protein to extravascular that induce tissue inflammation and soft tissue fibrosis process. In case of constriction band, the lymph trapped in the lower extremity, so it also requires surgical procedure.Patient and Method : We reported 2 cases, a woman 71 years old with right limb lymphedema with vulva polyp and a man 58 years old with constriction band on chronic left limb lymphedema and right limb poliomyelitis. We conducted circumference measurement of afected limb 5 minutes after application compression bandage in first two weeks. Case one had quiet good result with compression bandage only while in case two continued with surgical procedure consist of mass reduction using suction-assisted lipectomy, z-plasty constriction band release continue with excise skin redundancy. In both patients pressure garment used for daily treatment.Results : Both patients gave aceptable result on compression bandage in acute case and in chronic case was continued with surgery. Summary : Management for lymphedema can be done by conservative therapy in acute case when edema is in pitting formor combined with surgery when in chronic case, then pressure.